Construction of Mathematical Model between HIV-AIDS and Lesbian, Gay, Bisexual, and Transgender (LGBT) Transmission in a Population. (May 2020) - Sriningsih, R; Helma,; Putra, A A; Yuniarti, E; Soleh, M
Abstract: Human Immunodeficiency Virus (HIV) is a virus that attacks and damages the immune system of the human body so that it is easily attacked by various diseases. A collection of diseases that attack the body is called AIDS. HIV-AIDS is very contagious and deadly. Until now, there is no medicine, serum, vaccine that can cure sufferers of the HIV. HIV-AIDS infection is transmitted through 3 ways: vertically (from mother to child), sexual relations (homosexual, heterosexual and transsexual), and horizontally through inter-blood contact (sharing of contaminated needles, transfusion of contaminated blood, etc.). Sexual intercourse is the biggest cause of transmission. This research discussed construction of mathematical model of HIV-AIDS and LGBT transmission based on the interaction between infected and susceptible individuals in a population.